Assessment of Ocimum basilicum as Potentially Fruit Flies Attractant - Selma M. O. Abdullah; Amani M. K.Abbas; Hind A. Ali; Faiza M. Abdelmagid; Abubaker H. M. Adam (Journal of Agronomy Research, 2020)
The Basil plant (Ocimumbasilicum L) is an annual herb; belongs to family Lamiaceae. It is found to be an important source for Methyl Eugenol (ME), the fruit flies attractant. This study was carried out at Shendi area with main objective to assess the amount of ME extracted from Ocimumbasilicumplant to evaluate its potentiality as fruit fly attractant. Plants of basil were grown till to maturity, then the differential harvest of leaves, flower and seeds were chemically investigated for volatilome. Five basil formulations (paste and powder of leaves, paste and powder of flowers, isolated ME from basil oil) were used for trapping potential of Bactrocera spp in mango orchards, as compared to the synthetic ME. The oil was extracted using Soxhlet apparatus, steam and water distillation, and analyzed using GCMS. The results revealed that highest extracted oil percentages was obtained from flowers, leaves, seed and stem were 5.75%, 3.03%, 0.02% and 0.21% respectively. Moreover, the basil traps catch was found to be lower compared with that of the control traps. Furthermore, when extracted ME from basil plant was compared with the standard synthetic, it gave lower catch fruit flies numbers, but the difference was not significant (>0.05). In conclusion, the basil raw derivates are confirmed not to be attractive for flies but the oil distillable from the leaves could be in force of its attractant ME contents and insecticide potency.
Keywords: Basil